Answer:
Multiply both sides of the equation by -2
Distribute -1/2 over (x+4)
Explanation:
we have
![-(1)/(2)(x+4)=6](https://img.qammunity.org/2020/formulas/mathematics/high-school/20gln3ydxn4frusb1iec6abppm08mff0w0.png)
Method 1
Multiply both sides of the equation by -2 ------> Step 1
![(x+4)=6*(-2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4psp10m4rpce9bn7pus3r9kzn2d6ot8dg0.png)
![(x+4)=-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/chbu0v86h5t3cqvt4xk06eyr9fga0ivm3m.png)
Subtract 4 from both sides of the equation
![x=-12-4=-16](https://img.qammunity.org/2020/formulas/mathematics/high-school/texp4cv3fgcn5y5jy69xfyxhneq0z9triy.png)
Method 2
Distribute -1/2 over (x+4)-------> Step 1
![-(1)/(2)x-2=6](https://img.qammunity.org/2020/formulas/mathematics/high-school/hircu3fm72yv1z32dszptfl8lrlfiv98pa.png)
Multiply both sides of the equation by -2
![x+4=6(-2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/asaynxrnz0ynzuycbnt82y4vpo7dtr50dr.png)
![x+4=-12](https://img.qammunity.org/2020/formulas/mathematics/high-school/nda20w4s0ft983pvgp99v2ifv11v5qixzx.png)
Subtract 4 from both sides of the equation
![x=-12-4=-16](https://img.qammunity.org/2020/formulas/mathematics/high-school/texp4cv3fgcn5y5jy69xfyxhneq0z9triy.png)